Na "teia da vida" - eu, eles e a natureza: práticas pedagógicas sobre a natureza na educação infantil em Manaus - Souza, Rosane Miranda de (2019)
This study aims to analyze the conceptions related to nature among children of a preschool in the municipality of Manaus through the contributions of Science Education. With the intention of approaching answers, we analyze the pedagogical practices developed at school, related to Nature. We identified the theoretical sources in the legal documents of this stage of basic education, checking the north for the composition of its curriculum and the process of development of educational plans focused on nature. It was also observed the understanding of the classroom teacher, which we take as reference of the research, to know about his theoretical base and his pedagogical practice on this subject. We dialogue and interact with the children, developing activities that bring us closer and make them more comfortable to contribute with their speeches and perceptions about our object of study. The research was developed in the first semester of 2018, having as participants: eighteen children and 1 teacher of the II period, in a kindergarten in the city of Manaus. Bringing for analysis the theme Nature is of great relevance, given the impacts that the action of man causes in the natural environment, having a direct influence on the life and survival of societies on planet Earth. Reflecting on this perspective with this age group is essential, since the child should be encouraged from an early age to wake up to reflect on surrounding situations, in order to change behaviors that may contribute to the maintenance and preservation of natural resources. We base our methodological approach on the qualitative approach of research in education, presenting a dialectical character, understanding that social reality can be considered from the perspective of the relationship phenomenon and essence. In this way, we use data collection instruments such as semi-structured interviews with the teacher, observation of the pedagogical practices in the reference room and the realization of a pedagogical intervention through a didactic sequence with the creation of a “Green Space” in the courtyard. from school. Divided into three chapters, this research covered the theoretical foundation that underlies the concepts and subjects approached, observation and records in locus, analysis of data obtained. After the development of the activities, we noticed the change of several concepts previously present and later reformulated. Thus, we consider that activities that provide more direct experiences with natural elements contribute to the process of building more meaningful knowledge. Keywords: Science Education; Conceptions; Nature.